2015
DOI: 10.1016/j.rmed.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Age-related and historical changes in the clinical characteristics of sarcoidosis in Japan

Abstract: Elderly patients at diagnosis had various extrathoracic involvement including eye, skin, and cardiac lesions. Moreover, the age at diagnosis of sarcoidosis has continued to increase in both sexes, influencing the recent trends in clinical characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 28 publications
7
42
1
Order By: Relevance
“…We also found, as expected, an increased risk of sarcoidosis in black women compared with white women, with very similar estimates to those previously reported (6). Sarcoidosis has often been described as a disease occurring most commonly in younger adults, although there is some recent evidence of an increasing age at diagnosis in various populations (25,26) as well as differences in age at onset by race (27). In a U.S. population, the peak in annual incidence in white women was observed at age 40 to 49 years and a decade earlier in black women (6).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found, as expected, an increased risk of sarcoidosis in black women compared with white women, with very similar estimates to those previously reported (6). Sarcoidosis has often been described as a disease occurring most commonly in younger adults, although there is some recent evidence of an increasing age at diagnosis in various populations (25,26) as well as differences in age at onset by race (27). In a U.S. population, the peak in annual incidence in white women was observed at age 40 to 49 years and a decade earlier in black women (6).…”
Section: Discussionsupporting
confidence: 90%
“…A recent study in Japan found that in women, only the second peak was still observed in the last decade (25). In the current study, women were already aged 25 to 44 years at baseline, and incidence in young adulthood could not be assessed; however, our results are consistent with an increase in sarcoidosis incidence after the age of 50 years for women.…”
Section: Brief Communicationsupporting
confidence: 63%
“…Even though it was previously reported that the presence of hypercalcemia increases after 45 years of age [19], another study did not find differences in calcium values among elderly patients (≥65 years) [5]. We did not find a significant difference in serum calcium levels between groups.…”
Section: Discussioncontrasting
confidence: 92%
“…[123] It typically affects women in the age group from 20 to 60 years. It is diagnosed pathologically by the presence of noncaseating granulomas on biopsy of the lesion and presents in one or more of the following ways – pulmonary involvement in the form of hilar adenopathy or reticular shadows or extrapulmonary involvement in the form of eye/joint/skin/cardiac/central nervous system lesions.…”
Section: Discussionmentioning
confidence: 99%